Investigation of α-cluster Transfer in Peripheral Collisions of 40Ca (12.3 MeV/nucleon) + 27Al using the MARS Spectrometer - Giannitsa, Chrysi; Souliotis, George A.; Depastas, Theo; Rodrigues, Marcia Dias; Roeder, Brian; Alafa, Alex; Adsley, Philip; Gkatzogias, Konstantinos; Koulouris, Stergios; Mabiala, Justin; Zhu, Zhe; Bonasera, Aldo (HNPS Advances in Nuclear Physics, 2026)
Peripheral heavy-ion collisions at energies from the Coulomb barrier to the Fermi regime offer a unique environment for studying 𝛼-cluster transfer and nucleon-exchange processes. We present a preliminary study of 𝛼-cluster transfer from the reaction 40Ca (12.3 MeV/nucleon) + 27Al, that was performed at the Cyclotron Institute of Texas A&M University using the MARS recoil separator. Projectile-like fragments resulting from 𝛼-cluster transfer were identified with a Si detector telescope located at the focal plane of MARS. Production cross sections are extracted and compared with calculations with the Deep Inelastic Transfer (DIT) model. This procedure aims to provide a foundation for systematic comparison with appropriate theoretical models, leading to further insights into direct transfer mechanisms and clustering phenomena.